Preparation method of high-heat-resistance aluminum alloy

The coated aluminum powder is prepared by electroless plating and subjected to thermal isostatic pressing or hot extrusion treatment to form nano-scale alumina and AlFeNiCu heat-resistant phases, which solves the problem of poor heat resistance performance of traditional aluminum alloys in medium and high temperature intervals, significantly improving Its heat resistance and high temperature stability are achieved.

CN119464810AActive Publication Date: 2025-02-18HEFEI UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411576167.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-18
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Traditional aluminum alloy materials have poor heat resistance in medium and high temperature ranges, and it is difficult to meet the strict requirements of high temperature and high strength. The main reason is that the process characteristics lead to low solid solubility of elements, making it difficult to form a sufficiently high precipitation phase, and precipitation at high temperatures. The phase will be roughened, resulting in performance degradation.

Method used

Copper-clad aluminum powder, iron-clad aluminum powder and nickel-clad aluminum powder were prepared by electroless plating. After mixing, light oxidation and vacuum-clad shell were carried out, followed by hot isostatic pressing or hot extrusion densification to form nano-scale aluminum oxide and The AlFeNiCu heat-resistant phase ensures its uniform distribution and stable existence.

Benefits of technology

It significantly improves the heat resistance of aluminum alloy, suppresses high-temperature creep, enhances the high-temperature strength and stability of the alloy, and meets the application needs of high-temperature and high-strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464810A_ABST
    Figure CN119464810A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-heat-resistance aluminum alloy, and belongs to the technical field of nonferrous metal manufacturing. Copper-clad aluminum composite powder, iron-clad aluminum composite powder and nickel-clad aluminum composite powder are prepared through a chemical plating method, the powder is mixed according to a certain proportion, slightly oxidized in air and then subjected to vacuum sheathing, and a sheathing powder billet is subjected to hot isostatic pressing or hot extrusion densification treatment; in the densification process, a dual process of internal oxidation and nano heat-resistant phase precipitation is further carried out, and finally two nano heat-resistant phases, namely Al2O3 and an AlFeNiCu intermetallic compound, are formed in the aluminum alloy, so that the heat resistance of the aluminum alloy is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nonferrous metal manufacturing, and in particular relates to a method for preparing a high heat-resistant aluminum alloy. Background Art

[0002] Aluminum alloy materials are widely used in the fields of automobiles, aerospace, etc. due to their light weight, high strength, wear resistance and corrosion resistance, low density, high specific strength and good heat resistance. With the increasing requirements for the development of green environmental protection and circular economy, the heat resistance of aluminum alloys in weapons, ships, aviation, aerospace, automobiles and other industries has become more stringent. Although most aluminum alloy materials have good comprehensive mechanical properties at room temperature, the high temperature softening problem of aluminum alloys has always been a key shortcoming that restricts the structural design and service safety of parts in the medium and high temperature range. Traditional aluminum alloy materials are difficult to meet the stringent requirements of high temperature resistance and high specific strength in some fields. For example, for the representative 7075 aluminum alloy, the tensile strength of the alloy is only 30% and 10% of room temperature at 200℃ and 300℃. For the most commonly used cast heat-resistant aluminum alloys, such as A319, A380, ZL702A and other alloys that have been successfully commercialized in the field of automobile manufacturing, they cannot meet the requirements of new high-power engines (operating temperature 300-400℃) or other higher heat-resistant fields. The main reason is that its process characteristics lead to low element solubility, making it difficult to form a precipitation phase with a high enough volume fraction in the aluminum alloy matrix, and when the service temperature exceeds 200°C, the Mg content inside 2 Si、Al 2 Cu、Al 2 Strengthening phases such as CuMg will gradually coarsen, and the strengthening effect of the precipitated phase will be greatly reduced, resulting in a sharp drop in the high-temperature mechanical properties of the aluminum alloy.

[0003] Alumina, as a ceramic compound that can improve the heat resistance of aluminum alloys, has been used in the production of heat-resistant aluminum alloys. Its traditional preparation process is mainly to prepare aluminum oxide reinforced aluminum alloys by oxidizing the surface of aluminum alloy powder and then heating and extruding the powder. However, the aluminum oxide phase added by this method only exists on the surface of the alloy powder. After hot extrusion, it is impossible to achieve nano-scale addition of aluminum oxide phase and ensure the uniform dispersion of aluminum oxide phase in the alloy. In addition, AlFeNiCu is an intermetallic compound with high thermal stability. When this compound exists in aluminum alloy, it will not coarsen and grow below 400°C. Therefore, if nano-scale AlFeNiCu compounds can be added to aluminum alloys and ensure that the compounds can be evenly dispersed, the heat resistance of aluminum alloys can be greatly improved. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a high heat-resistant aluminum alloy, so as to solve the problem of poor high temperature resistance of aluminum alloy materials in the background technology.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A method for preparing a high heat-resistant aluminum alloy comprises the following steps:

[0007] Step 1, chemical plating on the surface of aluminum powder: copper plating, iron plating and nickel plating are performed on the surface of aluminum powder to prepare copper-clad aluminum powder, iron-clad aluminum powder and nickel-clad aluminum powder;

[0008] Step 2, slightly oxidized and then coated: copper-coated aluminum powder, iron-coated aluminum powder and nickel-coated aluminum powder are mixed in a mass ratio of 1:4-6:0.8-1.2, the mixed powder is kept in an air atmosphere at 180-220° C. for 20-40 minutes, filled into a pure aluminum coating, and vacuum-sealed to obtain a coated powder ingot;

[0009] By heat-insulating the mixed powder in the air, its surface is slightly oxidized to form copper oxide coated aluminum powder, iron oxide coated aluminum powder and nickel oxide coated aluminum powder. The degree of surface oxidation and the content of oxygen dissolved in the alloy in the subsequent process can be controlled by controlling the oxidation time and temperature. The mixed powder is then filled into a pure aluminum sleeve, vacuumed and sealed.

[0010] Step 3, densification of the metal billet: hot isostatic pressing or hot extrusion deformation of the encapsulated powder billet to obtain a high heat-resistant aluminum alloy billet;

[0011] The temperature of the hot isostatic pressing process is 500-540°C, the pressure is 100-200MPa, and the holding time is 1-3h;

[0012] The heating temperature of the hot extrusion deformation is 450-550° C., the heat preservation time is 1-2 hours, and the extrusion ratio is 10-15.

[0013] By hot isostatic pressing the coated powder ingot, the powder undergoes internal oxidation during the hot isostatic pressing process, that is, the aluminum in the composite powder undergoes a reduction reaction with copper oxide, iron oxide and nickel oxide, thereby forming a large amount of nano-scale aluminum oxide inside the aluminum alloy powder. In addition, the alloying elements Fe, Ni and Cu form a large amount of uniformly distributed nano-scale AlFeNiCu heat-resistant phases inside the powder through solid-state diffusion and reaction during the hot isostatic pressing process. The nano-scale Al 2 O 3 The AlFeNiCu heat-resistant phase can hinder the growth of alloy grains and the movement of dislocations, thereby inhibiting the high-temperature creep of the alloy. At the same time, the powders combine with each other during the hot isostatic pressing process to form a dense alloy ingot, thereby obtaining a dense high-heat-resistant aluminum alloy.

[0014] By subjecting the encapsulated powder billet to hot extrusion deformation, the alloy elements undergo the above-mentioned internal oxidation process during the heat preservation process, forming a large amount of dispersed Al 2 O 3 Nanoparticles and alloy elements form nano-scale AlFeNiCu heat-resistant phases inside the powder through diffusion and precipitation, and finally form a high heat-resistant aluminum alloy with uniform composition and dispersed precipitation phase. Then, the powders are metallurgically bonded through the hot extrusion process for densification. At the same time, the extrusion deformation breaks the structure of the powder to form more small-sized grains to further improve the performance of the alloy.

[0015] As a further solution of the present invention, the vacuum degree of the vacuum seal in step 2 is 10 -3 -10 -4 Pa.

[0016] The method for preparing the copper-clad aluminum powder comprises the following steps:

[0017] The atomized aluminum powder is immersed in a dilute alkaline solution for 0.5-1 min to remove the surface aluminum oxide, ethanol is added to the zinc sulfate solution to obtain an ethanol-zinc sulfate mixed solution, the filtered aluminum powder is immersed in the ethanol-zinc sulfate mixed solution for 20-30 min, and the aluminum powder is immersed in an acidic copper sulfate solution after filtration, and stirred for reaction at 40-80°C for 10-30 min. After the surface of the aluminum powder is fully copper-plated, the plating solution and powder are quickly filtered, and the filtered powder is washed and dried to obtain copper-clad aluminum powder.

[0018] As a further solution of the present invention, the dilute alkaline solution is a sodium hydroxide solution with a concentration of 0.03-0.1 mol / L.

[0019] As a further solution of the present invention, the concentration of the zinc sulfate solution is 20-80 g / L, and the ethanol is analytical grade ethanol.

[0020] As a further embodiment of the present invention, the volume of the ethanol is 5-15% of the volume of the zinc sulfate solution.

[0021] As a further solution of the present invention, the concentration of the acidic copper sulfate solution is 40-100 g / L, and 98% concentrated sulfuric acid is used to adjust the pH to 1.5-4.5.

[0022] The method for preparing the iron-clad aluminum powder comprises the following steps:

[0023] The atomized aluminum powder is immersed in a dilute alkaline solution for 0.5-1 min to remove the surface aluminum oxide, and a citric acid solution is added to the ferrous sulfate solution to obtain a citric acid-ferrous sulfate mixed solution. The filtered aluminum powder is immersed in the citric acid-ferrous sulfate mixed solution at 25-100°C for 1-20 min, and the powder is filtered out, washed, and dried to obtain the iron-clad aluminum powder.

[0024] As a further solution of the present invention, the concentration of the ferrous sulfate solution is 35-90 g / L, and the concentration of the citric acid solution is 4-40 g / L.

[0025] As a further solution of the present invention, the volume of the citric acid solution is 5-15% of the volume of the ferrous sulfate solution.

[0026] The method for preparing the nickel-coated aluminum powder comprises the following steps:

[0027] The atomized aluminum powder is immersed in a dilute alkaline solution for 0.5-1 min to remove the surface aluminum oxide, and ethanol is added to the nickel sulfate solution to obtain an ethanol-nickel sulfate mixed solution. The solution is filtered and immersed in an ethanol-nickel sulfate mixed solution, and stirred at 50-60°C until the solution becomes colorless. The reaction is continued for 25-35 min, and the powder is filtered, washed, and dried to obtain nickel-coated aluminum powder.

[0028] As a further solution of the present invention, the concentration of the nickel sulfate solution is 30-70 g / L, and the ethanol is analytical grade ethanol.

[0029] As a further embodiment of the present invention, the volume of the ethanol is 5-15% of the volume of the nickel sulfate solution.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The present invention provides a method for preparing a high heat-resistant aluminum alloy, wherein copper-clad aluminum composite powder, iron-clad aluminum composite powder and nickel-clad aluminum composite powder are prepared by chemical plating, the powders are mixed in a certain proportion and slightly oxidized in the air before vacuum encapsulation, the encapsulated powder billet is subjected to hot isostatic pressing or hot extrusion densification treatment, and a dual process of internal oxidation and precipitation of nano heat-resistant phases further occurs during the densification process, and finally Al is formed in the aluminum alloy. 2 O 3 and AlFeNiCu intermetallic compounds, two nanoscale heat-resistant phases, can significantly improve the heat resistance of aluminum alloys.

[0032] 2. The copper-clad aluminum composite powder, iron-clad aluminum composite powder and nickel-clad aluminum composite powder prepared by chemical plating can make the surface of the aluminum powder completely coated with copper, iron and nickel, thereby forming a structurally stable and tightly sealed shell outside the aluminum core powder. The thickness of the plated shell can be controlled by controlling the concentration of the chemical plating solution and the reaction time, thereby controlling the content of nano-alumina and nano-AlFeNiCu intermetallic compounds in the finally prepared heat-resistant aluminum alloy.

[0033] 3. Controlling the treatment time and temperature during the slight oxidation treatment of the powder can control the degree of oxidation on the powder surface and thus control the addition of oxygen, thereby controlling the content of highly heat-resistant and highly stable nano-aluminum oxide in the alloy during the subsequent internal oxidation process. Compared with the traditional hot extrusion process after aluminum powder oxidation, the internal oxidation process used in the process of the present invention forms a nano-scale aluminum oxide under the premise of controlling the aluminum oxide content, which greatly increases the amount of aluminum oxide and thus greatly improves the heat resistance of the aluminum alloy.

[0034] 4. During the hot isostatic pressing and hot extrusion process, the alloying elements Fe, Ni, and Cu diffuse and solid solution precipitate. Due to the large specific surface area of ​​the powder and the small powder particle size, the diffusion and solid solution process of the alloy components are relatively easy, thereby forming a uniformly dispersed AlFeNiCu heat-resistant phase. Moreover, since the AlFeNiCu heat-resistant phase is formed by a solid-state reaction, its size is small, reaching the nanometer level. After further hot forming process, these heat-resistant phase particles pin and hinder the dislocation movement generated by the hot forming process, thereby improving the heat resistance of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The present invention will be further described below in conjunction with the accompanying drawings.

[0036] Figure 1 are microstructure images of aluminum alloy ingots prepared in Example 1 of the present invention and Comparative Example 1; Figure 1 Figure (a) is a microstructure image of the high heat-resistant aluminum alloy prepared in Example 1; Figure 1 Figure (b) is an image of the aluminum alloy microstructure obtained by conventional method in Comparative Example 1;

[0037] Figure 2 It is a bar graph of the initial hardness of the two alloys and the hardness test after the aluminum alloy ingots prepared in Example 2 of the present invention and Comparative Example 1 were kept at 350° C. for 100 hours. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] A method for preparing a high heat-resistant aluminum alloy comprises the following steps:

[0040] Step 1, chemical plating on the surface of aluminum powder: copper plating, iron plating and nickel plating are performed on the surface of aluminum powder to prepare copper-clad aluminum powder, iron-clad aluminum powder and nickel-clad aluminum powder;

[0041] The method for preparing the copper-clad aluminum powder comprises the following steps:

[0042] The atomized aluminum powder is immersed in a dilute alkaline solution for 0.5-1min to remove the surface aluminum oxide, and ethanol is added to a zinc sulfate solution with a concentration of 20-80g / L to obtain an ethanol-zinc sulfate mixed solution (the volume of ethanol is 5-15% of the amount of the zinc sulfate solution), and the aluminum powder after filtration is immersed in the ethanol-zinc sulfate mixed solution for 20-30min. After filtration, the aluminum powder is immersed in an acidic copper sulfate solution (with a concentration of 40-100g / L, and 98% concentrated sulfuric acid is used to adjust the pH value to 1.5-4.5), and the reaction is stirred at 40-80°C for 10-30min. After the surface of the aluminum powder is fully copper-plated, the plating solution and the powder are quickly filtered, and the filtered powder is washed and dried to obtain the copper-clad aluminum powder.

[0043] The method for preparing the iron-clad aluminum powder comprises the following steps:

[0044] The atomized aluminum powder is immersed in a dilute alkaline solution for 0.5-1 min to remove the surface aluminum oxide, and a citric acid solution with a concentration of 4-40 g / L is added to a ferrous sulfate solution with a concentration of 35-90 g / L to obtain a citric acid-ferrous sulfate mixed solution (the volume of the citric acid solution is 5-15% of the volume of the ferrous sulfate solution), and the filtered aluminum powder is immersed in the citric acid-ferrous sulfate mixed solution, immersed at 25-100° C. for 1-20 min, and the powder is filtered out, washed, and dried to obtain iron-clad aluminum powder.

[0045] The method for preparing the nickel-coated aluminum powder comprises the following steps:

[0046] The atomized aluminum powder is immersed in a dilute alkaline solution for 0.5-1 min to remove the surface aluminum oxide, and ethanol is added to a nickel sulfate solution with a concentration of 30-70 g / L to obtain an ethanol-nickel sulfate mixed solution (the volume of ethanol is 5-15% of the amount of the nickel sulfate solution), and the aluminum powder after filtration is immersed in the ethanol-nickel sulfate mixed solution, stirred at 50-60° C. until the solution becomes colorless, and the reaction is continued for 25-35 min. The powder is filtered out, washed, and dried to obtain nickel-coated aluminum powder.

[0047] Step 2, slightly oxidized and then packaged: Copper-clad aluminum powder, iron-clad aluminum powder and nickel-clad aluminum powder are mixed in a mass ratio of 1:4-6:0.8-1.2. The mixed powder is kept in an air atmosphere at 180-220°C for 20-40 minutes, then filled into a pure aluminum package and evacuated to a vacuum degree of 10 -3 -10 -4 Pa, vacuum sealed to obtain the encapsulated powder ingot;

[0048] Step 3, densification of the metal billet: the sheathed powder billet is subjected to hot isostatic pressing at a temperature of 500-540°C, a pressure of 100-200 MPa, and a holding time of 1-3 h, or hot extrusion deformation at a heating temperature of 450-550°C, a holding time of 1-2 h, and an extrusion ratio of 10-15 to obtain a high heat-resistant aluminum alloy billet.

[0049] Example 1

[0050] A method for preparing a high heat-resistant aluminum alloy comprises the following steps:

[0051] Step 1, chemical plating on the surface of aluminum powder: copper plating, iron plating and nickel plating are performed on the surface of aluminum powder to prepare copper-clad aluminum powder, iron-clad aluminum powder and nickel-clad aluminum powder;

[0052] The method for preparing the copper-clad aluminum powder comprises the following steps:

[0053] The atomized aluminum powder is immersed in a sodium hydroxide solution with a concentration of 0.06 mol / L for 0.81 min to remove the surface aluminum oxide, and ethanol is added to a zinc sulfate solution with a concentration of 50 g / L to obtain an ethanol-zinc sulfate mixed solution (the volume of ethanol is 10% of the amount of the zinc sulfate solution), and the aluminum powder after filtration is immersed in the ethanol-zinc sulfate mixed solution for 25 min. After filtration, the aluminum powder is immersed in an acidic copper sulfate solution (with a concentration of 70 g / L, 98% concentrated sulfuric acid to adjust pH=3), and stirred at 60° C. for 20 min. After the surface of the aluminum powder is fully copper-plated, the plating solution and the powder are quickly filtered, and the filtered powder is washed and dried to obtain copper-clad aluminum powder;

[0054] The method for preparing the iron-clad aluminum powder comprises the following steps:

[0055] The atomized aluminum powder is immersed in a sodium hydroxide solution with a concentration of 0.06 mol / L for 0.8 min to remove the surface aluminum oxide, and a citric acid solution with a concentration of 28 g / L is added to a ferrous sulfate solution with a concentration of 65 g / L to obtain a citric acid-ferrous sulfate mixed solution (the volume of the citric acid solution is 10% of the volume of the ferrous sulfate solution), and the aluminum powder after filtration is immersed in the citric acid-ferrous sulfate mixed solution, and immersed at 60° C. for 12 min, and the powder is filtered out, washed, and dried to obtain iron-clad aluminum powder;

[0056] The method for preparing the nickel-coated aluminum powder comprises the following steps:

[0057] The atomized aluminum powder is immersed in a sodium hydroxide solution with a concentration of 0.06 mol / L for 0.8 min to remove the surface aluminum oxide, and ethanol is added to a nickel sulfate solution with a concentration of 50 g / L to obtain an ethanol-nickel sulfate mixed solution (the volume of ethanol is 10% of the amount of the nickel sulfate solution), and the aluminum powder after filtration is immersed in the ethanol-nickel sulfate mixed solution, stirred at 55° C. until the solution becomes colorless, and the reaction is continued for 30 min, and the powder is filtered out, washed, and dried to obtain nickel-coated aluminum powder;

[0058] Step 2: Slightly oxidized and then packaged: Copper-clad aluminum powder, iron-clad aluminum powder and nickel-clad aluminum powder are mixed in a mass ratio of 1:5:1. The mixed powder is kept in an air atmosphere at 200°C for 20 minutes, then filled into a pure aluminum package and evacuated to a vacuum degree of 10 - 4 Pa, vacuum sealed to obtain the encapsulated powder ingot;

[0059] Step 3: Densification of metal billet: The coated powder billet is subjected to hot isostatic pressing at a temperature of 530° C., a pressure of 150 MPa, and a holding time of 2 h to obtain a high heat-resistant aluminum alloy billet.

[0060] Example 2

[0061] A method for preparing a high heat-resistant aluminum alloy comprises the following steps:

[0062] Step 1, chemical plating on the surface of aluminum powder: copper plating, iron plating and nickel plating are performed on the surface of aluminum powder to prepare copper-clad aluminum powder, iron-clad aluminum powder and nickel-clad aluminum powder;

[0063] The preparation methods of the copper-clad aluminum powder, iron-clad aluminum powder and nickel-clad aluminum powder are the same as those in Example 1;

[0064] Step 2: Slightly oxidized and then packaged: Copper-clad aluminum powder, iron-clad aluminum powder and nickel-clad aluminum powder are mixed in a mass ratio of 1:5:1. The mixed powder is kept in an air atmosphere at 200°C for 30 minutes, then filled into a pure aluminum package and evacuated to a vacuum degree of 10 - 4Pa, vacuum sealed to obtain the encapsulated powder ingot;

[0065] Step 3, densification of the metal billet: subjecting the encapsulated powder billet to hot extrusion deformation at a temperature of 500° C., a holding time of 1.5 h, and an extrusion ratio of 13 to obtain a high heat-resistant aluminum alloy billet.

[0066] Comparative Example 1

[0067] A conventional smelting and casting method is adopted, and the alloy proportions are weighed in the same manner as in Example 1 while considering the burnout rate. The raw materials include pure aluminum block, pure fine iron wire, pure copper block and pure nickel block. First, the iron wire is placed at the bottom of a graphite crucible and then a pure aluminum block is placed on it. The mixture is heated to 800°C and kept warm for 0.5h. The mixture is then cooled to 750°C, and the copper block and the nickel block are added and allowed to stand for 10min. The mixture is then degassed and slag removed and allowed to stand for another 10min. Finally, the solution is cast into a metal mold preheated to 250°C to obtain a conventional molten cast aluminum alloy.

[0068] The microstructure images of the aluminum alloy ingots prepared in Example 1 and Comparative Example 1 are as follows: Figure 1 As shown, Figure 1 Figure (a) is a microstructure image of the high heat-resistant aluminum alloy prepared in Example 1; Figure 1 Figure (b) is the microstructure image of the aluminum alloy obtained by conventional method in Comparative Example 1. Figure 1 It can be seen from Figures (a) and (b) that a large number of fine Al 2 O 3 and AlFeNiCu precipitates. These dispersed precipitates can not only significantly improve the strength and hardness of the alloy, but also minimize the decrease in the plasticity and toughness of the alloy. They exist stably under high temperature conditions and hinder the movement of dislocations, reducing the possibility of grain growth, thereby maintaining the strength and stability of the alloy material at high temperatures. In contrast, the precipitates in the alloy ingot prepared by the traditional process in Figure (b) are not only coarse in size but also show regional aggregation, which significantly weakens the plasticity and toughness of the alloy. At the same time, these coarse precipitates are also difficult to cause obvious hindrance to the movement of dislocations at high temperatures. Therefore, the high-temperature strength and stability of the alloy are far inferior to those of the heat-resistant aluminum alloy prepared by the process of the present invention.

[0069] After the aluminum alloy ingots prepared in Example 2 and Comparative Example 1 were simultaneously kept at 350°C for 100 hours, the initial hardness of the two alloys and the hardness after keeping were as follows: Figure 2The Vickers hardness of the original high heat-resistant aluminum alloy (prepared in Example 2) is 150.3, and after 100 hours of heat preservation, the hardness value is 143.6, which is still much higher than the initial hardness of 110.7 and the hardness of 62.4 after heat preservation of the aluminum alloy obtained by the conventional method (prepared in Comparative Example 1). It fully shows that the high temperature heat resistance of the high heat-resistant aluminum alloy obtained by the process of the present invention is greatly improved.

[0070] The present invention prepares copper-clad aluminum composite powder, iron-clad aluminum composite powder and nickel-clad aluminum composite powder, mixes the powders in a certain proportion, slightly oxidizes them, and then vacuum encapsulates them. The encapsulated powder ingot is densified by hot isostatic pressing or hot extrusion. During the densification process, a dual process of internal oxidation and precipitation of nano heat-resistant phase occurs. Finally, Al is formed in the aluminum alloy. 2 O 3 and AlFeNiCu intermetallic compounds, two nanoscale heat-resistant phases, can significantly improve the heat resistance of aluminum alloys.

[0071] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high heat-resistant aluminum alloy, characterized in that: The following steps are involved: Step 1, chemical plating on the surface of aluminum powder: copper plating, iron plating and nickel plating are performed on the surface of aluminum powder to prepare copper-clad aluminum powder, iron-clad aluminum powder and nickel-clad aluminum powder; Step 2, slightly oxidized and then coated: copper-coated aluminum powder, iron-coated aluminum powder and nickel-coated aluminum powder are mixed in a mass ratio of 1:4-6:0.8-1.2, the mixed powder is kept in an air atmosphere at 180-220° C. for 20-40 minutes, filled into a pure aluminum coating, and vacuum-sealed to obtain a coated powder ingot; Step 3: Densification of metal billet: hot isostatic pressing or hot extrusion deformation is performed on the encapsulated powder billet to obtain a high heat-resistant aluminum alloy billet.

2. The method for preparing a high heat-resistant aluminum alloy according to claim 1, characterized in that: The temperature of the hot isostatic pressing process is 500-540° C., the pressure is 100-200 MPa, and the holding time is 1-3 hours.

3. The method for preparing a high heat-resistant aluminum alloy according to claim 1, characterized in that: The heating temperature of the hot extrusion deformation is 450-550° C., the heat preservation time is 1-2 hours, and the extrusion ratio is 10-15.

4. The method for preparing a high heat-resistant aluminum alloy according to claim 1, characterized in that: The method for preparing the copper-clad aluminum powder comprises the following steps: The aerosolized aluminum powder is immersed in a dilute alkaline solution for 0.5-1 min, ethanol is added to the zinc sulfate solution to obtain an ethanol-zinc sulfate mixed solution, the filtered aluminum powder is immersed in the ethanol-zinc sulfate mixed solution for 20-30 min, and the filtered aluminum powder is immersed in an acidic copper sulfate solution, stirred and reacted at 40-80° C. for 10-30 min, and the powder is filtered out, washed, and dried to obtain copper-clad aluminum powder.

5. The method for preparing a high heat-resistant aluminum alloy according to claim 4, characterized in that: The concentration of the zinc sulfate solution is 20-80 g / L, and the volume of the ethanol is 5-15% of the volume of the zinc sulfate solution.

6. The method for preparing a high heat-resistant aluminum alloy according to claim 4, characterized in that: The concentration of the acidic copper sulfate solution is 40-100 g / L, and 98% concentrated sulfuric acid is used to adjust the pH to 1.5-4.

5.

7. The method for preparing a high heat-resistant aluminum alloy according to claim 1, characterized in that: The method for preparing the iron-clad aluminum powder comprises the following steps: The atomized aluminum powder is immersed in a dilute alkaline solution for 0.5-1 min, a citric acid solution is added to the ferrous sulfate solution to obtain a citric acid-ferrous sulfate mixed solution, the filtered aluminum powder is immersed in the citric acid-ferrous sulfate mixed solution at 25-100° C. for 1-20 min, the powder is filtered out, washed, and dried to obtain iron-coated aluminum powder.

8. The method for preparing a high heat-resistant aluminum alloy according to claim 7, characterized in that: The concentration of the ferrous sulfate solution is 35-90 g / L, the concentration of the citric acid solution is 4-40 g / L, and the volume of the citric acid solution is 5-15% of the volume of the ferrous sulfate solution.

9. The method for preparing a high heat-resistant aluminum alloy according to claim 1, characterized in that: The method for preparing the nickel-coated aluminum powder comprises the following steps: The atomized aluminum powder is immersed in a dilute alkaline solution for 0.5-1 min, ethanol is added to the nickel sulfate solution to obtain an ethanol-nickel sulfate mixed solution, the filtered aluminum powder is immersed in an ethanol-nickel sulfate mixed solution, stirred at 50-60° C. until the solution becomes colorless, the reaction is continued for 25-35 min, the powder is filtered out, washed, and dried to obtain nickel-coated aluminum powder.

10. The method for preparing a high heat-resistant aluminum alloy according to claim 9, characterized in that: The concentration of the nickel sulfate solution is 30-70 g / L, and the volume of the ethanol is 5-15% of the volume of the nickel sulfate solution.

Citation Information

Patent Citations

  • Nickel package aluminum powder and preparing method thereof

    CN103433485A

  • Preparation method and application of aluminum-based conductive powder

    CN111318688A

  • Silver copper oxide contact material and preparation method thereof

    CN115927899A

  • Preparation method of high-heat-resistance aluminum-iron alloy

    CN117300116A

  • Nickel-coated aluminum powder and preparation method thereof

    CN117467991A